FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN ALAT KONTRASEPSI PADA WANITA USIA SUBUR DI PUSKESMAS NGESREP KELURAHAN NGESREP KECAMATAN BANYUMANIK SEMARANG - Wulandari, Priharyanti (STIKES Widya Husada Semarang, 2012)
FACTORS RELATED TO THE SELECTION OF CONTRACEPTION IN WOMEN OF CHILDBEARING AGE NGESREP VILLAGE IN HEALTH DISTRICT NGESREP BANYUMANIK SEMARANG There are several factors that influence the selection of an IUD and the family planning decisions, the social culture, religion / beliefs, family support and knowledge. The purpose of this study to determine the factors associated with the selection of contraception in women of childbearing age in the health center Ngesrep. The study was a descriptive correlation, the number of respondents and as many as 66 samples were taken by using purposive sampling technique. Engineering data analysis using Chi Square analysis with Î± = 0.05. The results showed that there is a relationship between confidence with the selection of contraception (Ïvalue = 0.015 < 0,05). There was no association between family support with the selection of contraception (Ïvalue = 1.000 > 0,05). There is a relationship between the selection of contraceptive knowledge (Ïvalue = 0.019 < 0,05). There is no relationship between the social economy election contraception (Ïvalue = 0.120 > 0,05). KeywordsÂ Â Â : Selection of Contraception, Female Age Fertile